After the end of art : contemporary art and the pale of history - Danto, Arthur C. (New Jersey : Princeton University Press, 1999)
Ch. 1 Introduction: Modern, Postmodern, and Contemporary##Ch. 2 Three Decades after the End of Art##Ch. 3 Master Narratives and Critical Principles##Ch. 4 Modernism and the Critique of Pure Art: The Historical Vision of Clement Greenberg##Ch. 5 From Aesthetics to Art Criticism##Ch. 6 Painting and the Pale of History: The Passing of the Pure##Ch. 7 Pop Art and Past Futures##Ch. 8 Painting, Politics, and Post-Historical Art##Ch. 9 The Historical Museum of Monochrome Art##Ch. 10 Museums and the Thirsting Millions##Ch. 11 Modalities of History: Possibility and Comedy
boek